Polypharmacy and the Potential Occurrence of Drug – Drug Interactions (DDIS) Among Geriatric Outpatients in Wangaya Regional General Hospital - Steven Jonathan; Raden Ayu Tuty Kuswardhani (Indonesian Journal of Global Health Research, 2026)
Number of elderly across the world is increasing over the year.  Among the elderly, physical and biological changes along with increasing number of diseases contribute to multiple medications. Polypharmacy in geriatric patients increases the risk of adverse drug reactions (ADRs) and drug-drug interactions (DDIs). Objective: This study aims to evaluate polypharmacy and potential DDIs occurrence among geriatric outpatients. A Retrospective observational study was conducted in Geriatric Outpatient Clinic at Wangaya Regional General Hospital. Data was collected using medical records from May – June 2025. DDIs were identified and classified using Lexicomp Drug Interactions database. Data distribution and statistical analyzes were performed using Spearman correlation test. Statistical hypothesis tests with p-value  less than 0.05 were considered statistically significant. This study involves 167 patients. Majority of the patients (47.3%) are in the young elderly group. Among the patients, 50.3% was considered as minor polypharmacy, 44.9% as major polypharmacy, and 1.2% as excessive polypharmacy. Most of DDIs type found in our study was Type C DDIs (45.9%) followed by Type B (31.9%). We found a statistically significant association between number of comorbidities, polypharmacy and DDIs. High prevalence and significant correlation were found between polypharmacy and potential occurrence of DDIs were found among geriatric outpatients. The finding of this study indicates the need for further research to develop strategies that can reduce the occurrence of polypharmacy and DDIs.